2007
DOI: 10.1016/j.jchromb.2007.01.032
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive and rapid liquid chromatography/tandem mass spectrometric assay for the quantification of chloroquine in dog plasma

Abstract: A simple, sensitive and rapid liquid chromatography/tandem mass spectrometric (LC-MS/MS) method was developed and validated for quantification of chloroquine, an antimalarial drug, in plasma using its structural analogue, piperazine bis chloroquinoline as internal standard (IS). The method is based on simple protein precipitation with methanol followed by a rapid isocratic elution with 10 mM ammonium acetate buffer/methanol (25/75, v/v, pH 4.6) on Chromolith SpeedROD RP-18e reversed phase chromatographic colum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…The precursor ion and product ion mass spectrums are illustrated in Figure 1. The MRM transition of CQ was in accordance with the reported result (Singhal 2007). The declustering potential, collision energy, collision cell entrance, and exit potentials were optimized sequentially with MRM mode.…”
Section: Optimization Of Lc-ms/ms Conditionssupporting
confidence: 77%
See 1 more Smart Citation
“…The precursor ion and product ion mass spectrums are illustrated in Figure 1. The MRM transition of CQ was in accordance with the reported result (Singhal 2007). The declustering potential, collision energy, collision cell entrance, and exit potentials were optimized sequentially with MRM mode.…”
Section: Optimization Of Lc-ms/ms Conditionssupporting
confidence: 77%
“…In recent decades, LC-MS=MS has become a popular and highly efficient technique for the trace analysis in bioassay especially for pharmacokinetic and toxicological studies. Recently, Puran Singhal et al (2007) reported a method for determining CQ in human and dog plasma using LC-MS=MS. An, Hodel et al (2009) developed an LC-MS=MS for the simultaneous determination of 14 antimalarials including CQ in human plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the run time of the method was only 2.4 min with the use of UPLC, which further increased the throughput. Various methods are reported in literature for the quantitation of amodiaquine (Stepniewska et al 2009), chloroquine (Hodel et al 2009;Singhal et al 2007) and chlorthalidone (Khuroo et al 2008;Salvadori et al 2009) in plasma. However, all the reported methods use time and resource-intensive extraction methods or have a long run time.…”
Section: Discussionmentioning
confidence: 99%
“…The C18 column was the most frequently used columns in previously published research [7][8][9][10][12][13][14] and we have investigated the peak shape and response of several C18 columns in the optimization process. With additives of 5 mM ammonium formate and formic acid (0.015∼0.1% formic acid) in mobile phase system consisting of acetonitrile and water, chloroquine did not reserve on an Eclipse Plus C18 column (5 μm, 100 × 4.6 mm, Agilent, USA) and the retention time remained almost unchanged (∼1.8 min) with different proportion of acetonitrile ranged between 13 and 70%.…”
Section: Lc-ms Methods Developmentmentioning
confidence: 99%
“…Singhal [14] Zuluaga-Idarraga [13] Cheomung [10] Internal standard Chloroquine-d4 Piperazine bis chloroquinoline [14] published an LC-MS/MS method for the detection of chloroquine in dog plasma for the first time. A structural analog instead of deuterated isotope internal standard (IS) and a simple protein precipitation by methanol were employed in this study.…”
Section: Our Assaymentioning
confidence: 99%